Integrative taxonomy reveals the historically poorly defined armoured catfish Hypostomus variipictus (Ihering 1911), from the upper rio Paraná basin, Brazil (Siluriformes, Loricariidae) - Azevedo, Filipe Manoel; Zawadzki, Cláudio Henrique; Soria, Thatiana Vanessa; Fabrin, Thomaz Mansini Carrenho; Oliveira, Alessandra Valéria De; Prioli, Sônia Maria Alves Pinto; Prioli, Alberto Jose (Journal of fish biology, 2021)
In a recent expedition to the rio Grande basin, a tributary of the rio Paraná in southern Brazil, individuals of the armoured catfish genus Hypostomus with a peculiar and beautiful colour pattern composed of pale vermiculations on the head and four to five horizontal stripes on the flanks were collected. Initially, the specimens were identified as a colour morph of the pale‐spotted H. margaritifer. However, when we compared their partial cytochrome C oxidase subunit I (COI) mitochondrial gene to sequences of some typically pale‐spotted H. margaritifer, the striped specimens were genetically distinct. Further analysis of the striped individuals revealed that they are the poorly known but valid species Hypostomus variipictus, which was described by Ihering in 1911 from the rio Pardo, a tributary of the rio Grande, upper rio Paraná basin, in São Paulo State, Brazil. Since its descriptions, no robust taxonomic work has been published concerning this species. In this study, the newly sampled population was compared to the original description and to the holotype of H. variipictus, providing the foundation for a complete redescription, proper diagnosis, and first live colour illustration and description of the previously hidden H. variipictus.